The anthropological conceptualization of the indio in Cusco (1942-1973) - Aguilar León, César (2019)
This article will examine the causes, sources and processes of the anthropological conceptualization of the concept of indio —understood as object of study— taken place in Cusco, from the institutional foundation of the discipline in 1942 to its first great crisis in 1973. In that regard, I propose that said processes of conceptualization were determined by the social and political conditions surrounding anthropologists, in connection to the trending anthropological theory at the time and the institutional situation of the discipline. All this, in relation to specific ideological contexts —such as the indigenisms— and sociopolitical contexts —such as social revolts.